2013
DOI: 10.1016/j.freeradbiomed.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of oxidative stress study V: Ozone exposure of rats and its effect on lipids, proteins, and DNA in plasma and urine

Abstract: Ozone exposure effect on free radical-catalyzed oxidation products of lipids, proteins and DNA in the plasma and urine of rats was studied as a continuation of the international Biomarker of Oxidative Stress Study (BOSS) sponsored by NIEHS/NIH. The goal was to identify a biomarker for ozone-induced oxidative stress and to assess whether inconsistent results often reported in the literature might be due to the limitations of the available methods for measuring the various types of oxidative products. The time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…It is important to stress that lipid peroxides are unstable derivatives from the oxidation of unsaturated fatty acids and decompose to form reactive carbonyl molecules, such as malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) [85,89]. These two products are abundant biomarkers of lipid peroxidation [85,90].…”
Section: Effects On Biological Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to stress that lipid peroxides are unstable derivatives from the oxidation of unsaturated fatty acids and decompose to form reactive carbonyl molecules, such as malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) [85,89]. These two products are abundant biomarkers of lipid peroxidation [85,90].…”
Section: Effects On Biological Membranesmentioning
confidence: 99%
“…It is important to stress that lipid peroxides are unstable derivatives from the oxidation of unsaturated fatty acids and decompose to form reactive carbonyl molecules, such as malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE) [85,89]. These two products are abundant biomarkers of lipid peroxidation [85,90].Membrane-bound proteins are also involved in the process of lipid peroxidation. Aldehyde products, such as MDA and 4-HNE, react with amine and thiol groups of membrane protein, causing several damages, including inactivation of enzymes.…”
mentioning
confidence: 99%
“…Ozone is a strong oxidizing agent and has been linked to lung inflammation, and alveolar epithelial damage. It has been suggested that these damages are initiated by free radicals formed from the decomposition of secondary ozonides, a reaction product of ozone with unsaturated lipids [6]. Ozone also has been reported to induce damage to cellular DNA via free radical mediated reactions.…”
Section: Smogmentioning
confidence: 99%
“…2. Recent technical advances used to detect and identify ROS/RNS biomarkers and free radical metabolism are electron spin resonance (ESR), the immuno-spin trapping technique (IST), and radioimmunoassay (RIA) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The cellular antioxidant system, designed to prevent damage to tissue, is composed of antioxidant enzymes and other non-enzymatic compounds that have the ability to reduce different chemical structures [21]. These compounds are responsible for maintaining the balance between pro-and antioxidant agents and alleviating OS (see Table 1).…”
Section: Introductionmentioning
confidence: 99%